Fotometría de llama, un método preciso, seguro y fiable para la determinación de sodio en matrices de pasabocas fritos a base de maíz - Jhojan Mauricio Madrid-Molina; Bryan Stevens Mena-Delgado; Leonardo Alexis Alonso Gómez (TecnoLógicas, 2025)
In the food industry, it is crucial to validate analytical methods for the testing of nutrients and components in processed food products, especially with the recent inclusion of warning labels. This paper introduces a novel methodology for determining sodium levels in fried corn-based snacks. The main objective of this study was to determine the reliability of the method in consistently delivering accurate results. The methodology involved a thorough validation of the flame photometry analytical method to precisely measure the sodium content in corn-based snack foods. The equipment results were linearized for the specific analyte, and its accuracy was determined by calibration curves at four control points using two sodium standards. One standard was standardizedcontrol, and the second was prepared by directly diluting the food matrix of interest. The limits of the equipment for sodium detection and quantification were determined. Accuracy was evaluated using experimental recovery percentages. The results of the method’s standardization were evaluated for 10 months by analyzing 150 corn-based snack samples and obtaining measurement data from stable sodium tests compared to the data reported on the packaging. The results indicated the accuracy and linearity of the method through a linear regression curve and analysis of variance, as well as homogeneity and homoscedasticity by applying the t-statistic and the Cochran Q test. Finally, the conclusion is that the method provides fast, safe, reliable, and accurate results. The sample analyzed is in compliance with the regulations for low-sodium foods without a warning label.